Utilization of planting white oyster mushroom media wastes (Pleurotus ostreatus) fermented by starbio on local sheep male performances - T S Simorangkir; T H Wahyuni; M Tafsin; I Sembiring; N Ginting (Talenta Publisher, 2018)
The Utilization of Planting White Oyster Mushroom Media Wastes (Pleurotus ostreatus) fermented by Starbio on Local Sheep male Performances. White osyter mushroom media waste is one of agricultural waste can be utilized sheep.The research have been conducting for 3 month ago. The purpose of this research is to find out and learn the influence of the use of white osyter mushroom media waste in fermentation with starbio performances on male local sheep. This study used 20 male local sheep. The method used was a complete randomized design which consist of four treatments and five replications. The treatment consists of 4 types with utilization of planting white oyster mushroom media wastes different P0, P1, P2, and P3 are 0%, 10%, 20%, and 30% respectively.The result of this reseacrh showed that P0, P1, P2, and P3 treatment were significanly differences (P≤0,01) in feed consumption, average daily gain but had no significanly (P≥0,05) in feed convertion ration ration. Based on this research can be concluded that the utilization of media wastes planted white oyster mushroom (Pleurotus ostreatus) fermented by Starbio on 10% level increase feed consumption, average daily gain and income over feed cost local sheep male.